2021
DOI: 10.1002/aepp.13206
|View full text |Cite
|
Sign up to set email alerts
|

Crop insurance participation and cover crop use: Evidence from Indiana county‐level data

Abstract: This study examines whether crop insurance participation reduces incentives to use cover crops in corn and soybean production. To achieve this objective, we utilize 2006–2015 county‐level longitudinal data with information on cover crop adoption and crop insurance participation for the State of Indiana. Cover crop adoption information is collected from a remote sensing (satellite‐based) data set of soil health practices. Linear fixed effect (FE) models and instrumental variable FE models are used in the empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…According to DeLay (2019), the instrument captures how much a county sees its effective subsidy rates increase and hence can be used to estimate the variation in insured acreage due only to changes in government policy and not to contemporaneous land-use decisions. Connor et al (2021) adopted a version of this instrument that used a policy exposure measure constructed as the proportion of insured acres for coverage levels.…”
Section: Available Instruments For Crop Insurancementioning
confidence: 99%
See 1 more Smart Citation
“…According to DeLay (2019), the instrument captures how much a county sees its effective subsidy rates increase and hence can be used to estimate the variation in insured acreage due only to changes in government policy and not to contemporaneous land-use decisions. Connor et al (2021) adopted a version of this instrument that used a policy exposure measure constructed as the proportion of insured acres for coverage levels.…”
Section: Available Instruments For Crop Insurancementioning
confidence: 99%
“…Regardless if crop insurance demand is specified as a dependent or independent variable, researchers may consider using instrumental variables to generate the requisite exogenous variation for credible econometric identification (Roberts et al 2006; Walters et al 2012; Falco et al 2014; Deryugina and Konar 2017; Connor et al 2021). However, finding a suitable instrument is often challenging.…”
Section: Introductionmentioning
confidence: 99%
“…CC acres have 70% chance of persistence after a 3‐year contract period in the Mississippi Delta region. This may be attributed to several beneficial aspects of CCs, such as water quality improvement, soil erosion reduction, yield improvement, resilience against weather extremities, tax breaks, discounts in crop insurance rates, and reduction in the need for herbicides and pesticides (Aglasan et al., 2023; Blanco‐Canqui, 2018; Connor et al., 2021; Kaye & Quemada, 2017; Myers & Wilson, 2023; Snapp et al., 2005). The results are consistent with the general trend of CCs acreage.…”
Section: Resultsmentioning
confidence: 99%
“…The only studies we found that use satellite-based cover crop data are Seifert et al (2018), Chen et al (2021) Connor et al (2022), andPark et al (2022).…”
Section: Prevented Planting In Crop Insurancementioning
confidence: 99%
“…In general, one cannot say that one data source is superior to another, and each (OpTIS or AgCensus) is a reasonable source of cover crop adoption data (i.e., the estimated correlation between the OpTIS and the AgCensus cover crop areas is 0.67 based on the study by Hagen et al, 2020). It should also be noted that the OpTIS data now has a track record of being used in agricultural economics research published in peer‐reviewed journals (Chen et al, 2021; Connor et al, 2022).…”
Section: Data Descriptionmentioning
confidence: 99%